2013
DOI: 10.1093/pasj/65.4.88
|View full text |Cite
|
Sign up to set email alerts
|

Clumpy Outflows from Supercritical Accretion Flow

Abstract: A significant amount of matter in supercritical (or super-Eddington) accretion flow is blown away by radiation force, thus forming outflows; however, the properties of such radiation-driven outflows have been poorly understood. We have performed global two-dimensional radiaion-magnetohydrodynamic simulations of supercritical accretion flow onto a black hole with 10 or 10$^{8} M_{\odot}$ in a large simulation box of 514 $r_{\rm S} \times 514 r_{\rm S}$ (with $r_{\rm S}$ being the Schwarzschild radius). We confi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
138
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(155 citation statements)
references
References 60 publications
14
138
0
3
Order By: Relevance
“…The detection of such a wind is consistent with the predictions of super-Eddington accretion (Takeuchi et al 2013). The wind has a complex dynamical structure with an ionization state that increases with the outflow velocity, which indicates launching from different regions of the accretion disk.…”
Section: Discussionsupporting
confidence: 84%
“…The detection of such a wind is consistent with the predictions of super-Eddington accretion (Takeuchi et al 2013). The wind has a complex dynamical structure with an ionization state that increases with the outflow velocity, which indicates launching from different regions of the accretion disk.…”
Section: Discussionsupporting
confidence: 84%
“…where R c is the radius of the clump (∼5R g from simulations; Takeuchi et al 2013). For the same values as above, we can see that ∼1 per cent covering fraction is quite reasonable assuming only a single clump; in the limit of a greater number, this value will of course increase (dependent on the time-scales between clumps being launched).…”
Section: J Middleton Et Almentioning
confidence: 59%
“…The toy model of Middleton et al (2011a) ascribed the observed large amplitude, short time-scale (tens to thousands of seconds) variability seen in NGC 5408 X-1 to obscuration by individual clumps, generated through radiative-hydrodynamic instabilities in the wind (now reproduced in simulations; Takeuchi et al 2013Takeuchi et al , 2014. In the specific case of NGC 5408 X-1, this requires our line of sight to the inner regions to intercept the wind (see Middleton et al 2014a).…”
Section: On the Origin Of Variability In Ulxsmentioning
confidence: 99%
“…NGC 5907 ULX1 has a hard spectrum (classified as a "hard ultraluminous state" by Sutton et al 2013b), and so would be expected to be viewed at a low inclination. However, it may still be possible to reconcile dipping and a hard spectrum within this framework if our viewing angle lies close to the opening angle of the accretion flow, such that we are viewing the innermost regions through the uppermost atmosphere of the outer regions, which superEddington simulations predict to be dominated by a clumpy outflow (Takeuchi et al 2013). If NGC 5907 ULX1 is a standard ∼10  M stellar remnant, its extreme luminosity would suggest the opening funnel for the accretion flow would likely be quite narrow, and so the wind could well be close to our line of sight.…”
Section: Discussionmentioning
confidence: 99%